The CT assessment of uncovertebral joints degeneration in a healthy population - Huang, Tianji; Qin, Jie; Zhong, Weiyang; Tang, Ke; Quan, Zhengxue (European journal of medical research, 2021)
Background A retrospective study investigated the degeneration trend of uncovertebral joints in a healthy population based on CT assessment. Methods A total of 200 males and 160 females, aged 21–79 years old (50.82 ± 17.06), who underwent CT examination in our hospital from September 2020 to March 2021 were enrolled. Sixty patients were included in each age group. According to the Kellgren and Lawrence classification and CT was used to evaluate the uncovertebral joints degeneration in different groups. Results With the increase of age, the degeneration of each segment was gradually aggravated. The uncovertebral joints started degenerating in the 20 s, and the C5–6 is the most degenerative segment, followed by the C4–5 and C6–7. Significant degeneration occurred in each segment between the 40 s and 60 s and became more severe after the 70 s. Conclusions The modified Kellgren and Lawrence classification based on CT scan could provide a quantitative assessment of uncovertebral joints degeneration in a healthy population and could provide more details for artificial cervical arthroplasty.